Pengaruh Pemasaran Media Sosial dan Kualitas Pelayanan terhadap Kepuasan Pelanggan Pada Restoran Sushi Yay! Cimahi - Fitri Rahmatika; Inta Budi Setyanusa (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2026)
This study aims to determine the effect of social media marketing and service quality on customer satisfaction at Sushi Yay! Cimahi Restaurant. Social media marketing is used as a means of promotion and communication with customers, while service quality reflects the restaurant's ability to meet customer expectations. The research method used was quantitative with a descriptive and verification approach. Data were analyzed using validity tests, reliability tests, classical assumption tests, and multiple linear regression analysis. The results indicate that social media marketing has a positive and significant effect on customer satisfaction. Furthermore, service quality also has a positive and significant effect on customer satisfaction. Simultaneously, social media marketing and service quality have a significant effect on customer satisfaction at Sushi Yay! Cimahi Restaurant.